Associated aspects to the age at sexual initiation among adolescents: a quantitative study - Ana Luiza Vilela Borges; Elizabeth Fujimori (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
using survival analysis, we analyzed data from 363 both female and male 15 to 19 year-old adolescents enrolled in a family health unit in the east area of são paulo city. they filled a self-administered structured questionnaire at home in may 2007. results showed an statistical difference in the age of sexual initiation between women and men (15,2 and 14,3 years of age, respectively). sexual life onset showed to be an event that does not occur in a linear way during adolescence, but a gradual phenomenon that takes place from a specific age. multiple cox regression showed that variables associated to the age at sexual initiation among women were working as well as relating a non-rigid mother concerning to dating. variable associated to the age at sexual initiation among men was agreeing to the sentence "man can have sex no matter what because can't become pregnant". It was concluded that cultural, relational and demographical aspects can influence sexual initiation among adolescents.